2018
DOI: 10.1155/2018/7532403
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study on Low-Dose Aspirin versus Placebo Administration in Silent Brain Infarcts: The Silence Study

Abstract: Background We investigated low-dose aspirin (ASA) efficacy and safety in subjects with silent brain infarcts (SBIs) in preventing new cerebrovascular (CVD) events as well as cognitive impairment. Methods We included subjects aged ≥45 years, with at least one SBI and no previous CVD. Subjects were followed up to 4 years assessing CVD and SBI incidence as primary endpoint and as secondary endpoints: (a) cardiovascular and adverse events and (b) cognitive impairment. Results Thirty-six subjects received ASA while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…An increased number of infarct-like lesions as detected by MRI at the end of the study was seen in 16 subjects in the control group and two in the cilostazol group. 65 The two identified studies 64,65 are both small and even though a tendency to better clinical outcomes was seen in both studies, they provide insufficient support for a general recommendation of antiplatelet treatment in subjects with ccSVD to avoid new clinical events (Table 5), which only includes the study by Maestrini et al 64 because we did not consider the study of patient with diabetes mellitus by Shinoda-Tagawa et al 65 to be a "true" primary prevention study.…”
Section: Cilostazol Vs No Antithrombotic Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…An increased number of infarct-like lesions as detected by MRI at the end of the study was seen in 16 subjects in the control group and two in the cilostazol group. 65 The two identified studies 64,65 are both small and even though a tendency to better clinical outcomes was seen in both studies, they provide insufficient support for a general recommendation of antiplatelet treatment in subjects with ccSVD to avoid new clinical events (Table 5), which only includes the study by Maestrini et al 64 because we did not consider the study of patient with diabetes mellitus by Shinoda-Tagawa et al 65 to be a "true" primary prevention study.…”
Section: Cilostazol Vs No Antithrombotic Treatmentmentioning
confidence: 96%
“…One randomised, double blind placebo-controlled trial included patients !45 years with at least one silent brain infarct (SBI) but no previous clinical cerebrovascular events for randomization to aspirin 100 mg (n¼36) or placebo (n¼47). 64 The primary endpoint was the combined endpoint of ischaemic stroke, TIA, and new silent brain infarcts (SBIs) detected at MRI which had occurred in nine controls (19.1%) and two ). Findings should be interpreted with care as the number of incident ischaemic strokes and myocardial infarctions were small with wide confidence intervals including one.…”
Section: Aspirin Vs Placebomentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of nonsteroidal anti-inflammatory drugs (NSAIDs) have been demonstrated to reduce the incidence of AD and other neurodegenerative disorders in prospective trials and in model organisms (Vlad et al, 2008;Varvel et al, 2009;Tasaki et al, 2012;Zhang et al, 2018). The same studies also found NSAIDs protect against cardiovascular and cerebrovascular disease (Patrono, 2013;Maestrini et al, 2018) and several types of adult-onset cancer (Di Francesco et al, 2015). Other, non-pharmacological strategies commonly employed to reduce the risk of AD include supplementation of polyunsaturated, ω-3 fatty acids (Lim et al, 2005), physical activity (Roach et al, 2011), and cognitive engagement (Maci et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that patients with silent brain infarction have a higher risk of future stroke. Al- though the effectiveness of aspirin to prevent stroke has not been studied in this setting [9], a recent prospectively multicenter clinical trial has shown that silent cerebral infarction seems to be a negative prognostic factor and low-dose aspirin treatment might improve the prognosis [10]. Therefore, it seems appropriate to apply secondary stroke prevention strategies to silent stroke patients with modifiable risk factors for atherosclerosis.…”
Section: Case Reportmentioning
confidence: 99%